Ask Question
24 December, 23:23

Combining like terms

Simplify each expression

1.) (0b + 10) + 5 (b+2)

2.) - 7 (n + 3) - 8 (1 + 8n)

Rewrite each expression using the distributive property. Then simplify

1.) - 6 (3x - 8)

2.) (-m + 9) ( - 3)

3.) (3) (-6 - x)

4.) 2 (x - y + 1)

5.) 4 (6p + 2q - 2p)

6.) p (m + 2)

+1
Answers (1)
  1. 25 December, 00:02
    0
    Combine like terms with common variable to simplify an expression.

    1) (0b + 10) + 5 (b + 2) = 10 + 5b + 10 = 5b + 20

    2) - 7 (n + 3) - 8 (1 + 8n) = - 7n - 21 - 8 - 64n = - 71n - 29

    Use the distributive property to expand the expression.

    1) - 6 (3x - 8) = - 18x + 48

    2) (-m + 9) (-3) = 3m - 27

    3) 3 (-6 - x) = - 18 - 3x

    4) 2 (x - y + 1) = 2x - 2y + 2

    5) 4 (6p + 2q - 2p) = 24p + 8q - 8p = 16p + 8q

    6) p (m + 2) = pm + 2p
Know the Answer?